Managing Discourse: Medical Heresy, Integrative Medicine and the Therapeutic Touch Debate - Mackay, Kevin (My University, 2000)
In this thesis I examine the debate surrounding Therapeutic Touch, a controversial energetic healing modality being practiced by registered nurses in biomedical institutions across North America. The debate surrounding the therapy takes place within medical journals, popular media articles, and on the internet. Within the debate, definitions of illness etiology, appropriate treatment, patient management, and alternative therapy use are contested by Therapeutic Touch proponents and critics. Through discursive analysis, interviews with local participants in the debate, and participant observation within the TT community, I present an analysis of the issues being contested and of the discursive strategies used by proponents and critics within the debate. The debate is contextualized in two ways: first, as an instance of medical heresy, in which an alternative healing group arises within the orthodox medical community and struggles to maintain itself within biomedical discourse and institutions; second, I contextualize the debate as an example of the wider trend towards integrative medicine in North America. Integrative medicine sees alternative therapies being increasingly used within health care delivery systems, either by alternative practitioners, or by biomedical practitioners who have co-opted alternative techniques. I argue that Therapeutic Touch proponents have utilized several discursive strategies in presenting and arguing for their alternative healing model. These strategies surround the issues of professional legitimacy, scientific validity, and TT’s perception as religious or spiritual. Therapeutic Touch proponents manage their discourse by conforming it to orthodox biomedical discourse and by pursuing a strategy of professionalization. Through this management process, they have been able to maintain a marginal presence within biomedicine.
Keywords: medical heresy; integrative medicine; therapeutic touch debate; managing discourse